The surge in biosimilars: considerations for effective pharmacovigilance and EU regulation. (October 2018) - Calvo, Begoña; Martinez-Gorostiaga, Javier; Echevarria, Enrique
The development of biosimilars is growing rapidly, especially in Europe. They are a cost-effective alternative to original biological medicines and can help improve patient access to these therapies. The European Medicines Agency (EMA) has been the first to issue scientific guidelines related to regulatory requirements for the approval of biosimilars. These guidelines have been being updated in line with advances in analytical techniques and growing experience in the clinical use of these drugs. Given the complex nature of biological medicines, they pose a greater potential risk of immunogenicity than nonbiological medicines, and hence warrant special consideration. The risk management plan for biopharmaceuticals (innovator and biosimilar drugs) should be based on strengthening ongoing pharmacovigilance activities, especially in the post-approval period. This paper addresses regulatory issues related to the approval of biosimilars in Europe associated with safety considerations linked to the development and use of these medicines. We also discuss the issues of immunogenicity, interchangeability and traceability of biological medicines.